Deep-sea benthic foraminifera at a bauxite industrial waste site in the Cassidaigne Canyon (NW Mediterranean): Ten months after the cessation of red mud dumping - Fontanier, Christophe; Mamo, Briony; Mille, Déborah; Duros, Pauline; Herlory, Olivier (Comptes Rendus. Géoscience, 2020)
During an environmental survey performed in autumn 2016, living (stained) benthic foraminiferal faunas were investigated at 16 stations sampled within the Cassidaigne Canyon (NW Mediterranean Sea) and surrounding area and located between 265–2500 m water depth. For many decades, industrial bauxite residues of red mud have drained into the canyon via a submarine pipe, causing physical disturbance and chemical contamination. In January 2016, solid waste disposal ceased and was replaced with the dumping of a low-density liquid effluent. Our ecological observations at the 725 m-depth station closest to the Cassidaigne Canyon submarine pipe show the highest concentration of the opportunistic species, and a strongly altered benthic diversity. At the other fifteen stations, foraminiferal standing stocks and simple diversity decrease with decreasing food input to the seafloor and increasing water depth. There, foraminiferal composition with a minor contribution of stress-tolerant species echoes the overall meso-oligotrophic patterns of a relatively stable ecosystem.